2013
DOI: 10.1163/15707563-00002412
|View full text |Cite
|
Sign up to set email alerts
|

Ecological divergence between two evolutionary lineages of Hyla savignyi (Audouin, 1827) in Turkey: effects of the Anatolian Diagonal

Abstract: Most of Turkey's land area is covered by one of three biodiversity hotspots (Caucasus, Irano-Anatolian, and Mediterranean). Anatolia is one of the main corridors for postglacial colonization of Europe. Uncovering how populations of a species differ genetically and ecologically is important for understanding evolutionary processes. Here, I examined ecological information to define ecological divergence between two lineages of Hyla savignyi. Using ecological niche modeling, I determined whether the two genetical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…All models support this vicariance with different climatic preferences for lineages C and G of T. vermicularis, because lineage C (Figure 2 (2, 2A, 2B, 2C)) prefers drier habitats than does lineage G (Figure 3 (4, 4A, 4B, 4C)). Similarly, Gül (2013) showed that lineage 1 of Hyla savignyi appeared to be confined to warmer and drier habitats in the area east of the Anatolian Diagonal, whereas lineage 2 of Hyla savignyi was found in cooler and wetter regions. Nearly simultaneous phylogenetic splits introducing lineage E occurred during the Late Pliocene or Early Pleistocene at 3.0 Mya (2.4-4.3 Mya) (Kornilios et al, 2012).…”
Section: Discussionmentioning
confidence: 92%
“…All models support this vicariance with different climatic preferences for lineages C and G of T. vermicularis, because lineage C (Figure 2 (2, 2A, 2B, 2C)) prefers drier habitats than does lineage G (Figure 3 (4, 4A, 4B, 4C)). Similarly, Gül (2013) showed that lineage 1 of Hyla savignyi appeared to be confined to warmer and drier habitats in the area east of the Anatolian Diagonal, whereas lineage 2 of Hyla savignyi was found in cooler and wetter regions. Nearly simultaneous phylogenetic splits introducing lineage E occurred during the Late Pliocene or Early Pleistocene at 3.0 Mya (2.4-4.3 Mya) (Kornilios et al, 2012).…”
Section: Discussionmentioning
confidence: 92%
“…The north/east–south/west orientation of the diagonal provides the connection between the east‐west directed mountains of the Mediterranean and the Caspian Sea (Médail and Diadema, 2009; Ansell et al, 2011). The Anatolian Diagonal has been shown to serve as a barrier for some animal species (Gül, 2013; Vamberger et al, 2013) or as a diversification spot for other groups (Stümpel et al, 2016). However, as Davis (1971) already suggested, the Anatolian Diagonal might have served as a land bridge between east and west for plants.…”
Section: Discussionmentioning
confidence: 99%
“…They include the genus Ricotia (Özüdoğru et al, 2015) and the tribe Arabideae (Ansell et al, 2011; Karl et al, 2012; Karl and Koch, 2013). There are only a few other studies covering the biogeographic history of Anatolian and Irano‐Turanian plants (e.g., Font et al, 2009; Manafzadeh et al, 2016), though several animal groups are better represented (e.g., Bilgin et al, 2006; Gül, 2013). Therefore, more studies are needed in this area to understand both historical biogeographic patterns and the evolution of ecologically important plant characters.…”
mentioning
confidence: 99%
“…Hence the mountains of the Anatolian Diagonal connect the otherwise isolated mainly west-eastern oriented Anatolian mountain ranges (Ansell et al 2011). The Anatolian Diagonal has been regarded as a barrier for animals (Gül 2013, Vamberger et al 2013) and a migratory route for plant species (Ansell et al 2011, Mummenhoff et al 2001, Jordon-Thaden 2009, Karl & Koch 2013. Twenty-four percent of the Brassicaceae species occur in the Irano-Turanian region (Koch & Kiefer 2006) and it has been hypothesized to be the "ancestral area" or centre of origin for the entire Brassicaceae , Couvreur et al 2010, Franzke et al 2011, Warwick et al 2010, Hedge 1976).…”
Section: Introductionmentioning
confidence: 99%
“…The Anatolian Diagonal has been shown to serve as a barrier for some animal species (Gül 2013, Vamberger et al 2013 or as a diversification spot for other groups (Stümpel et al 2016). However, as Davis (1971) already suggested, the Anatolian Diagonal might have served as a land bridge between east and west for plants.…”
mentioning
confidence: 99%